The sum of the two numbers is $$\dfrac{-4}{3}$$. If one of the numbers is -5, find the other.

Asked by Sakshi | 1 year ago |  47

##### Solution :-

Let us note down the given details

Sum of two numbers = $$\dfrac{-4}{3}$$

One of the number = $$\dfrac{-5}{1}$$

By using the formula,

Other number = sum of number – given number

$$\dfrac{-4}{3}- \dfrac{-5}{1}$$

By taking LCM for 3 and 1 which is 3

$$\dfrac{-5}{1}=\dfrac{(-4×1 – -5×3)}{3}$$

= $$\dfrac{ (-4 + 15)}{3}$$

$$\dfrac{11}{3}$$

the other number is $$\dfrac{11}{3}$$

Answered by Aaryan | 1 year ago

### Related Questions

#### By what number should 1365 be divided to get 31 as quotient and 32 as remainder?

By what number should 1365 be divided to get 31 as quotient and 32 as remainder?

#### Which of the following statement is true / false?

Which of the following statement is true / false?

(i) $$\dfrac{ 2 }{ 3} – \dfrac{4 }{ 5}$$ is not a rational number.

(ii) $$\dfrac{ -5 }{ 7}$$ is the additive inverse of $$\dfrac{ 5 }{ 7}$$

(iii) 0 is the additive inverse of its own.

(iv) Commutative property holds for subtraction of rational numbers.

(v) Associative property does not hold for subtraction of rational numbers.

(vi) 0 is the identity element for subtraction of rational numbers.

#### If x = 4 / 9, y = – 7 / 12 and z = – 2 / 3, then verify that x – (y – z) ≠ (x – y) – z

If x = $$\dfrac{4 }{ 9}$$, y =$$\dfrac{-7 }{ 12}$$ and z = $$\dfrac{-2 }{ 3}$$, then verify that x – (y – z) ≠ (x – y) – z

If x = $$\dfrac{ – 4 }{ 7}$$ and y = $$\dfrac{2 }{ 5}$$, then verify that x – y ≠ y – x
Subtract the sum of $$\dfrac{ – 5 }{ 7} and\dfrac{ – 8 }{ 3}$$ from the sum of $$\dfrac{5 }{ 2} and \dfrac{– 11 }{ 12}$$